Disparities of Self-compassion and Job Satisfaction across Decision-Making Styles among Filipino Workers - Marielle R. Potente; Rochelle Anne U. Caraig; Kayze Kein B. Panibe; Jemerson Naceno Dominguez (Universitas Katolik Soegijapranata, 2023)
Self-compassion and job satisfaction of Filipino workers across their decision-making styles are constructs of the present study being presented in the field of work. This paper aimed to identify the decision-making style; describe and measure the degree of self-compassion and job satisfaction; and determine the difference in self-compassion and job satisfaction across decision-making styles among respondents. The General Decision-making Styles Questionnaire (GDSQ), Self-compassion Scale, and Job Satisfaction Survey were administered to 359 respondents who aged from 28-60 years old, regardless of gender, across different companies in Calabarzon. The respondents were employees from entry level positions, supervisors, as well as executive level positions. Results have shown that rational, intuitive, dependent, avoidant, spontaneous, and dependent were the decision-making styles among respondents. The degree of self-compassion was at a high level (M=142.78, SD=21.16), while the degree of job satisfaction showed respondents’ ambivalence towards their job (M=3.51, SD=0.46). The Multivariate Analysis of Variance (MANOVA) confirmed a significant difference (Fobt= 5.054**, p of 0.0001) in the self-compassion and job satisfaction across decision-making styles among Filipino workers and was validated by Fisher’s LSD as a post hoc test. Outcomes of the study is recommended as a basis in proposing intervention programs in human resource management and industrial psychology. Mixed-method research is recommended to strengthen the concepts of self-compassion and related variables in this study.